An assessment of quality, trust and usability of Indonesian agricultural journals / Bambang Winarko - Winarko, Bambang (2015)
Scientists and other scholars need information to support their research activities. This information must be of high quality for them to perform their tasks effectively. Journals are one of the communication media used for disseminating scholarly information. While there are international indexing services that rank the quality of journals, these indexes have limited applicability to local journals or those in local languages. Using the Indonesian Agency for Agricultural Research and Development (IAARD) as a case, this study examined the quality, trust, and usability of nine agricultural journals in Indonesia. It also produced journal rankings and compare the ranking resulted from different approaches. Three journal assessment approaches, namely, quality, trust, and usability were employed using revealed preference and stated preference studies. A total of 229 researchers returned the questionnaire on trust and usability of IAARD journals. In parallel, 674 articles were examined using bibliometrics analysis. The data was then examined for ranking and the differences among the journals. The data showed that there were a total of 840 authors for the sample examined, and the number of authors for each paper ranged from 1 to 9. The authors were from Indonesia and 10 other countries, and affiliated to 118 organizations. Plant science and production were the fields of knowledge with the highest number of articles. The articles had low selfcitation. The assessment found that journal quality index of IAARD journals reached 2.59. Jurnal Hortikultura, Jurnal Agro Ekonomi and Indonesian Journal of Agricultural Science are the top three journals with the highest journal quality index. Meanwhile, Trust index of IAARD journals was 3.26. Jurnal Penelitian Pertanian Tanaman Pangan achieved the highest trust of IAARD journals with the index value reached 3.44 followed by Indonesian Journal of Agricultural Science (3.40), and Jurnal Penelitian dan Pengambangan Pertanian (3.39). On the other hand usability index of IAARD journal is 1.96. Jurnal Enjiniring Pertanian is the journal with the highest usability index (2.19), followed by Jurnal Tanah dan Iklim with the usability index reached 2.03, Indonesian Journal of Agricultural Science and Jurnal Tanah dan Iklim have similar the usability index of 1.98. Indices of IAARD journals quality varied from 2.52 to 2.71. Jurnal Hortikultura (2.71) is ranked first among IAARD journals, followed by Indonesian Journal of Agricultural Science (2.66), Jurnal Penelitian Pertanian Tanaman Pangan (2.64), Jurnal Agro Ekonomi (2.63), Jurnal Tanah dan Iklim (2.64), Jurnal Penelitian dan Pengambangan Pertanian (2.57), Jurnal Ilmu Ternak dan Veteriner (2.61), Jurnal Penelitian Tanaman Industri (2.58), dan Jurnal Enjiniring Pertanian (2.52).